Retaining Scholarly Voices for the Profession: Doctoral Graduates as Agentic Constructors of Scholarship - Holmes, Barbara; Parker, DeJuanna; Mitchell, Charles; Fillman, Scott; Hurt, Sonya (Advances in Social Sciences Research Journal, 2024)
This qualitative study explored the exercise of academic identity and agency of five doctoral graduates. Each participant received a doctorate from programs that focus on the production of new knowledge after the degree is attained. The study yielded four emerging themes: Importance of Academic Community to Scholarly Engagement, Challenges of Post-Doctoral Life , Challenges to the Exercise of Scholarly Agency, and Need for Collaboration and Mentorship Opportunities, which precipitated the development of a new paradigm, Fillman’s Hierarchy of Agentic Construction.